PUFA Index Assessment of Dental Caries Severity in Children Living in Wetland Environments - Renie Kumala Dewi; Qurratul Aina; Ika Kusuma Wardani (Faculty of Dentistry, Universitas Islam Sultan Agung, 2026)
Background: Dental caries is a multifactorial disease that is a health problem in children. Children 5-9 years old have the highest caries prevalence. Untreated dental caries can be measured using the PUFA/pufa index. Sungai Kupang Village has acidic water with pH values ranging from 3.09-6.45 and an iron (Fe) content above the maximum allowable level of 1.044mm/ltr. Most people use wetland water in their daily lives, including for gargling after brushing their teeth. Brushing teeth with acidic water can reduce the surface hardness of tooth enamel, thereby increasing the risk of dental caries. Method: The study used a descriptive, cross-sectional design. The sampling technique used was purposive sampling. The sample of 148 children aged 5-9 years was visually examined with a dental mirror to assess the severity of dental caries using PUFA/pufa index criteria, including pulp involvement (P/p), ulceration (U/u), fistula (F/f), and Abscess (A/a). The research data were analyzed descriptively and presented as frequencies, percentages, and average PUFA/pufa. Result: PUFA/pufa index of untreated dental caries in the form of pulp involvement (P/p) was 3.0; ulceration (U/u) was 0.06; fistula (F/f) was 0.1, and abscess (A/a) was 0.02. The caries severity of untreated dental caries based on the PUFA/pufa index was 3.1. The 7-year-old age group and female gender had the highest average PUFA index. Conclusion: According to the average PUFA/pufa index, children 7 years old and female have the most severe untreated dental caries.